2022
DOI: 10.3389/fbioe.2022.836042
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Plant Extracts on Dentin Bonding Strength: A Systematic Review and Meta-Analysis

Abstract: Objective: To systematically review in vitro studies that evaluated the effects of plant extracts on dentin bonding strength.Materials and Methods: Six electronic databases (PubMed, Embase, VIP, CNKI, Wanfang and The Cochrane Library) were searched from inception to September 2021 in accordance with the Preferred Reporting Items for Systematic Reviews (PRISMA). In vitro studies that compared the performance of dental adhesives with and without the plant extracts participation were included. The reference lists… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 77 publications
0
2
0
Order By: Relevance
“…However, GA has strong cytotoxicity and its clinical application is limited ( Cilli and Prakki, 2009 ; Cai et al, 2018 ). Therefore, natural polyphenolic cross-linking agents derived from plants have attracted more and more attention due to their strong and low toxicity, such as proanthocyanidins (PA), epigallocatechin gallate (EGCG), etc ( Zhao et al, 2022 ). Studies have shown that naturally occurring polyphenolic compounds can interact with collagen fibers through phenolic hydroxyl and galloyl groups to form covalent, ionic, and hydrogen bonds.…”
Section: Introductionmentioning
confidence: 99%
“…However, GA has strong cytotoxicity and its clinical application is limited ( Cilli and Prakki, 2009 ; Cai et al, 2018 ). Therefore, natural polyphenolic cross-linking agents derived from plants have attracted more and more attention due to their strong and low toxicity, such as proanthocyanidins (PA), epigallocatechin gallate (EGCG), etc ( Zhao et al, 2022 ). Studies have shown that naturally occurring polyphenolic compounds can interact with collagen fibers through phenolic hydroxyl and galloyl groups to form covalent, ionic, and hydrogen bonds.…”
Section: Introductionmentioning
confidence: 99%
“…Cross-linking agents, like adhesives, increase the hardness of the HL collagen matrix as improved biomechanical properties of the dentin matrix increase resin-dentin bond durability (Cai et al, 2018). A previous meta-analysis evaluating the effects of plant extracts as a primer on dentin bonding strength demonstrated an improvement in the immediate bond strength of adhesive (Zhao et al, 2022). Nevertheless, whether collagen cross-linkers can provide stable and long-lasting bonding strength to the adhesive interface is still debatable.…”
Section: Introductionmentioning
confidence: 99%